2016
DOI: 10.5194/acp-16-1445-2016
|View full text |Cite
|
Sign up to set email alerts
|

How to most effectively expand the global surface ozone observing network

Abstract: Abstract. Surface ozone observations with modern instrumentation have been made around the world for more than 40 years. Some of these observations have been made as oneoff activities with short-term, specific science objectives and some have been made as part of wider networks which have provided a foundational infrastructure of data collection, calibration, quality control, and dissemination. These observations provide a fundamental underpinning to our understanding of tropospheric chemistry, air quality pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The second is located in a high-altitude basin known as the Altiplano, Bolivia (Rose et al 2015). Sofen et al (2016) indicated that the current monitoring network of surface O 3 (including low-altitude stations) is insufficient for measurements in key regions (China, India, Amazon, Africa, tropical oceans, and Southern Ocean) and suggested the establishment of 20 possible sites (10 island and 10 continental). A strategy should be implemented to facilitate observations of key species in areas in which few observatories are located.…”
Section: Recommendations For Future Atmospheric Monitoringmentioning
confidence: 99%
“…The second is located in a high-altitude basin known as the Altiplano, Bolivia (Rose et al 2015). Sofen et al (2016) indicated that the current monitoring network of surface O 3 (including low-altitude stations) is insufficient for measurements in key regions (China, India, Amazon, Africa, tropical oceans, and Southern Ocean) and suggested the establishment of 20 possible sites (10 island and 10 continental). A strategy should be implemented to facilitate observations of key species in areas in which few observatories are located.…”
Section: Recommendations For Future Atmospheric Monitoringmentioning
confidence: 99%
“…In situ and satellite observations provide a substantial amount of information on the present day tropospheric ozone distribution and its variability and trends over the recent past (Tarasick et al, 2017, hereinafter referred to as TOAR-Observations; Gaudel et al, 2017, hereinafter referred to as TOAR-Climate), but there are important gaps in our knowledge (Cooper et al, 2014). Many regions of the world, including remote oceans and continental areas like Africa, South America, the Middle East, and India, remain under-sampled leading to incomplete knowledge of the horizontal, vertical and temporal distribution of ozone (Oltmans et al, 2013;Cooper et al, 2014;Lin et al, 2015a;Sofen et al, 2016a). Furthermore, observational estimates of the preindustrial ozone burden are highly uncertain (TOAR-Observations) making it difficult to accurately quantify the preindustrial to present day ozone changes and the resulting radiative forcing on climate and air quality impacts.…”
Section: Referred To As Toar-surface Ozone Database)mentioning
confidence: 99%
“…One issue of representativeness relates to the fact that the atmosphere is not completely sampled (Sofen et al, 2016a(Sofen et al, , 2016bTOAR-Observations), meaning that there are important locations and times where there are no constraints for the model (e.g., a globally sparse distribution of monitoring stations, coarse vertical data from satellites, poor constraints on pre-industrial ozone). Given the incomplete sampling, the primary issue for representativeness where we have observations relates to the fact that the spatial and temporal resolutions of global models are necessarily coarse.…”
Section: Considerations For Model-observation Comparisonsmentioning
confidence: 99%
“…Prior attempts to summarize the global distribution of tropospheric ozone and its trends (e.g. Cooper et al, 2014;Sofen et al, 2016a) were limited to readily accessible data from large networks maintained by the World Meteorological Organisation, and North American, and European institutions, which introduced substantial geographical bias in the analyses. In the framework of TOAR the most comprehensive database possible of global surface ozone observations has been established at Forschungszentrum Jülich in Germany.…”
Section: Introductionmentioning
confidence: 99%